The Retarded Gastrulation Induced In Developing Sea Urchin Embryo By Rearing In D2O-Sea Water - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Abstract: The process of gastrulation was lingeringly proceeded in developing sea urchin embryo reared in 40% D2O-sea water (D2O-SW). In general, these embryo possessed large blastocoel, and occasionally developed with evagjnated gut. The micro surgical experiments confirmed that the postulated higher hydrostatic pressure of blastocoel was not responsible for gut evagination. Thus the alternative hypothesis, "stabilization" of micro tubular cytoskeleton in the filopodia of the secondary mesenchyme cells, and disharmony of cellular development remain the possible cause of gut evagination. This hypothesis, however are coincided with the fact that D2O strongly inhibited cell division and archenteron formation.